Clinical and paraclinical assessment of the efficacy of calcium carbonate, vitamin d3 and chitosan in the management of chronic renal failure in dogs - Florin Dan SIMIZ; Elena Daniela BRĂSLAȘU; Cristina VĂDUVA (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Chronic kidney disease (CKD) is the most commonly diagnosed renal condition in dogs, having a gradual and irreversible course. In this context, the present study aimed to evaluate the efficacy of a nutritional supplement containing calcium carbonate, vitamin D3, and chitosan, administered over a 60-day period to a group of 20 mixedbreed dogs (10 females and 10 males), aged between 8 and 12 years, diagnosed with CKD stages 1, 2 and 3, according to the IRIS classification. Supplement administration resulted in significant changes in hematological and biochemical parameters: a 4.14% increase in red blood cell count, a 34.18% increase in total serum protein concentration and a 55.18% increase in albumin levels. Concurrently, marked decreases were observed in key renal dysfunction markers: phosphorus (-53.7%), creatinine (-75.54%), SDMA (-48.1%), and urea (-71.7%). Pulsed Doppler ultrasound revealed a 48.6% reduction in the renal resistive index (RRI), suggesting improved renal perfusion. In addition to these favorable biochemical effects, clinical improvements were also reported, including reduced polyuria and polydipsia, increased appetite, and enhanced general health status. These findings suggest that the tested supplement may play a beneficial role in slowing CKD progression and supporting the metabolic and clinical condition of affected dogs, indicating promising therapeutic potential as an adjuvant in the management of this disease.